Agency of the personality of a pupil as an interdisciplinary scientific problem - Halyan, О. (Continuing Professional Education: Theory and Practice, 2019)
The article emphasizes the need to expand the categorical apparatus of the pedagogical science through the use of concepts belonging to other disciplines, but help to enrich the essential context of describing the position of a pupil in education and upbringing. It is about «agency of a personality». It is determined that having philosophical and psychological roots this category acquires a new meaning in connection with the analysis of its pedagogical aspect and recognition of this category as an interdisciplinary one. The author analyzed the relationship between the concepts «agent» and «agency». It is determined that their differentiation reflects different views on the determinants that allow us to refer to a person as an agent or describe his/her agency. Thus, agency is usually used in conjunction with the term «activity», «communication», «knowledge». Therefore, the agent manifests himself through externally specified circumstances and is externally controlled. Agency has internal causality, intentionality. The author of the article gives the definition of «agency». According to the author, it is a potential and (or) implemented ability to exercise autonomy, initiative, responsibility, creativity and freedom of choice in various spheres of life. And activity is seen as a systemically important factor that determines the operation of each of the attributes of agency. The author offered a structural and semantic model of agency of the pupil’s personality. It is represented as a multilevel system. It refers to a certain organization of educational environment, special conditions that ensure the formation of all the attributes of agency, and the spheres of its manifestation (educational activities, communicative activity, socially significant activities and self-knowledge).